Synthesis, Mesomorphic, and Solar Energy Characterizations of New Non-Symmetrical Schiff Base Systems - Alamro, Fowzia S.; Ahmed, Hoda A.; Gomha, Sobhi M.; Shaban, Mohamed (Frontiers in Chemistry, 2021)
New asymmetrical Schiff base series based on lateral methoxy group in a central core, (E)-3-methoxy-4-(((4-methoxyphenyl)imino)methyl)phenyl 4-alkoxybenzoate (An), were synthesized and their optical and mesomorphic characteristics were investigated. The lateral OCH3group was inserted in the central ring in ortho position with respect to the azomethine linkage. FT-IR, and NMR spectroscopy as well as elemental analyses were used to elucidate their molecular structures. Their mesomorphic behaviors were characterized by polarized optical microscopy (POM) and differential scanning calorimetry (DSC). These examinations indicated that all the designed series were monomorphic and possessed nematic (N) mesophase enantiotropically, except A12 derivative which exhibited monotropic N phase. A comparative study was made between the present investigated series (An) and their corresponding isomers (Bn). The results revealed that the kind and stability of the mesophase as well as its temperature range are affected by the location and special orientation of the lateral methoxy group electric-resistance, conductance, energy-gap, and Urbach-energy were also reported for the present investigated An series. These results revealed that all electrodes exhibit Ohmic properties and electric-resistances in the GΩ range, whereas the electric resistance was decreased from 221.04 to 44.83 GΩ by lengthening the terminal alkoxy-chain to n = 12. The band gap of the An series was reduced from 3.43 to 2.89 eV by increasing the terminal chain length from n = 6 to n = 12 carbons. Therefore, controlling the length of the terminal chain can be used to improve the An series’ electric conductivity and optical absorption, making it suitable for solar energy applications.